Facing the Planetary : Entangled Humanism and the Politics of Swarming - Connolly, William E. (Book collections on Project MUSE., 2017)
William E. Connolly expands his influential work on the politics of pluralisation, capitalism, fragility and secularism to address the complexities of climate change and to complicate notions of the Anthropocene. Focusing on planetary processes - including the ocean conveyor, glacier flows, tectonic plates and species evolution - he combines a critical understanding of capitalism with an appreciation of how such nonhuman systems periodically change on their own.